Chagas disease and globalization of the Amazon La enfermedad de Chagas y la globalización de la Amazonia - Roberto Briceño-León (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
The increasing number of autochthonous cases of Chagas disease in the Amazon since the 1970s has led to fear that the disease may become a new public health problem in the region. This transformation in the disease's epidemiological pattern in the Amazon can be explained by environmental and social changes in the last 30 years. The current article draws on the sociological theory of perverse effects to explain these changes as the unwanted result of the shift from the "inward" development model prevailing until the 1970s to the "outward" model that we know as globalization, oriented by industrial forces and international trade. The current article highlights the implementation of five new patterns in agriculture, cattle-raising, mining, lumbering, and urban occupation that have generated changes in the environment and the traditional indigenous habitat and have led to migratory flows, deforestation, sedentary living, the presence of domestic animals, and changes in the habitat that facilitate colonization of human dwellings by vectors and the domestic and work-related transmission of the disease. The expansion of Chagas disease is thus a perverse effect of the globalization process in the Amazon. El incremento de casos autóctonos de la enfermedad de Chagas en la Amazonia a partir de los años setenta hace temer que pueda convertirse en un novedoso problema de salud pública en la región. Este cambio del patrón epidemiológico de la enfermedad en la región amazónica debe ser explicado por las transformaciones ambientales y sociales que han ocurrido en los pasados treinta años. Este artículo utiliza la teoría sociológica de los efectos perversos para explicar esos cambios como el resultado indeseado del cambio de modelo de desarrollo "hacia adentro", que había existido hasta los años setenta, por otro "hacia fuera" que está orientado por las fuerzas de la producción y el comercio internacional que conocemos como globalización. El artículo destaca que la implantación de cinco nuevos patrones de ocupación agrícola, ganadero, minería, madera y urbano que han generado cambios en el medio ambiente y el hábitat indígena tradicional y que han provocado corrientes migratorios, deforestación, sedentarización de la población, presencia de animales domésticos y modificaciones en el hábitat que facilitan la colonización de las viviendas por los vectores y la transmisión domestica y laboral de la enfermedad. La expansión de la enfermedad de Chagas es un efecto perverso del proceso de globalización de la Amazonia.